Macrophages originated IL-33/ST2 inhibits ferroptosis in endometriosis via the ATF3/SLC7A11 axis - Qiong Wu; Zongwen Liang; Jing Jiang; Xiaoming Feng; Jinming Liu; Zongfeng Zhang; Honglin Wang; Ning Wang; Yanling Gou; Zhi Li; Yingying Cao (Cell Death and Disease, 2023)
Abstract Endometriosis is a gynecological inflammatory disease that is linked with immune cells, specifically macrophages. IL-33 secreted from macrophages is known to accelerate the progression of endometriosis. The periodic and repeated bleeding that occurs in women with endometriosis leads to excess iron in the microenvironment that is conducive to ferroptosis, a process related to intracellular ROS production, lipid peroxidation and mitochondrial damage. It is suggested that eESCs may specifically be able to inhibit ferroptosis. However, it is currently unclear whether IL-33 directly regulates ferroptosis to influence the disease course in endometriosis. In this study, eESCs co-cultured with macrophages or stimulated with IL-33/ST2 were observed to have increased cell viability and migration. Additionally, IL-33/ST2 decreased intracellular iron levels and lipid peroxidation in eESCs exposed to erastin treatment. Furthermore, IL-33/ST2 treatment resulted in a notable upregulation in SLC7A11 expression in eESCs due to the downregulation of negative transcription factor ATF3, thereby suppressing ferroptosis. The P38/JNK pathway activated by IL-33/ST2 was also found to inhibit the transcription factor ATF3. Therefore, we concluded that IL-33/ST2 inhibits the ATF3-mediated reduction in SLC7A11 transcript levels via the P38/JNK pathway. The findings reveal that macrophage-derived IL-33 upregulates SLC7A11 in eESCs through the p38/JNK/ATF3 pathway, ultimately resulting in protection against ferroptosis in eESCs. Moreover, we conducted an experiment using endometriosis model mice that showed that a combination of IL-33-Ab and erastin treatment alleviated the disease, showing the promise of combining immunotherapy and ferroptosis therapy.